The biotransformation of glucosinolates : a bacterial perspective : a thesis presented in partial fulfilment of the requirements for the degree of PhD in Food Technology at Massey University, Manawatū, New Zealand - Mullaney, Jane Adair (Massey University, 2013)
Epidemiological studies have shown an association between the consumption of cruciferous vegetables and a reduced risk of certain types of cancers, in particular, colon, bladder and bowel. This is thought to be due to the conversion of glucosinolates present in the vegetables into bioactive isothiocyanates which in turn stimulate a host response involving detoxification pathways. Conversion of glucosinolates is catalysed by the enzyme myrosinase, which is co-produced by the plant but stored in separate tissue compartments and brought together when the tissue is damaged. Myrosinase activity can be reduced or lost during storage of vegetables and is often inactivated by cooking. However, in the absence of active plant myrosinase, bacteria are capable of carrying out a myrosinase-like activity on glucosinolates producing isothiocyanates or nitriles. This thesis examined the bacterial biotransformation of glucosinolates by two lactic acid bacteria and Escherichia coli Nissle 1917, all three considered beneficial bacteria. They were compared with a known glucosinolate-metabolising gut bacterium Enterobacter cloacae in vitro, in vivo and ex vivo to determine the bacterial responses to glucosinolates and what the products of their glucosinolate metabolism might be. Exposure of the host to beneficial bacteria and glucosinolates resulted in induction of the host detoxification enzyme quinone reductase which was elevated in bladder tissue for all dietary intervention groups consuming glucosinolates and beneficial bacteria, alone or combined. In vitro, Nissle reduced alkylsulfinyl glucosinolates and their hydrolysis products through redox to alkylthiols and in vivo, the host microbiota responded similarly. In vivo, the host response to alkylthiol nitriles was to oxidise these back again to alkylsulfinyl nitriles and oxidise further resulting in some nitriles being irreversibly oxidised to the sulfone. The association between consumption of cruciferous vegetables and reduced cancer of the colon, bladder and bowel is only that; an association. However, the results of this thesis demonstrated that bladder tissue was affected by beneficial bacteria and glucosinolates alone or together, which suggests that both exert a protective effect that could be measured by elevated quinone reductase, a biomarker for cancer chemoprevention.
Keywords: Glucosinolates; Biotransformation (Metabolism); Food Technology